The Economics of Open Science and Ukraine’s Prospective Place in It - Kharlamova, Ganna (Ekonomika, 2025)
This article presents the evaluation of the factors influencing the adoption of Open Access (OA) within the Open Science (OS) paradigm, utilizing statistical dynamics of OA publications across EU countries from 2000 to 2022. The study employs econometric modeling to test a set of hypotheses regarding the percentage of articles in OA, including: the proportion of freely accessible research outputs; the regulatory impact of OA declarations; state-driven OA publication; overall scientific development fostering collaboration; OA rates among top universities; young researchers engagement; and internet penetration as a facilitator of OA dissemination. The analysis reveals the growth trajectory in dynamics of OA. The EU model forecasts an increase in the percentage of OA articles from approximately 50% in 2022 to 70% by 2030, contingent on sustained investment and policy alignment.These hypotheses form a model initially developed for EU countries, providing a framework to assess Ukraine’s academic publishing landscape and its evolving position within OS. A SWOT and PESTLE analysis is conducted to evaluate the financing of Ukrainian science, identifying the broader implications of OA implementation. Prospects for Ukraine’s integration into the OS paradigm are outlined, emphasizing the necessity of overcoming unique challenges such as war-related disruptions.
Keywords: open science; model; financing; open access; development; growth